Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $G$ be a group and $a,b \in G$. Prove that if $a^{2}=e$ and $ab^{4}a=b^{7}$, then $b^{33}=e$, where $e$ is the identity of a group $G$.

share|improve this question
    
More generally, $a^2=e$ and $a b^p a = b^q$ implies $b^{p^2}=b^{q^2}$. You can use anon's proof for this. –  Martin Brandenburg Oct 3 '13 at 12:58

3 Answers 3

So $\rm ab^4a=b^7$. Apply $\rm a$ on left and right to get $\rm ab^7a=b^4$. Then, using symmetry in calculation,

$$\rm ab^{4\times7}a=\begin{cases}(ab^4a)^7=(b^7)^7=b^{49} \\[3pt] \rm(ab^7a)^4=(b^4)^4=b^{16} \end{cases}$$

and so $\rm b^{49}=b^{16}\iff e=b^{49-16}=b^{33}$.

Note that since $\rm a^2=e\iff a=a^{-1}$, the map $\rm\Phi_a: x\mapsto axa=axa^{-1}$ is conjugation, which is a special type of automorphism. In particular $\rm\Phi_a(xy)=\Phi_a(x)\Phi_a(y)$ and thus $\rm\Phi_a(x^{n})=\Phi_a(x)^n$ for any elements $\rm x,y$ and integer ${\rm n}\in{\bf Z}$. We employed the latter exponential distributivity above.

share|improve this answer
    
thank you so much –  nameless Mar 22 '13 at 8:23
3  
As an exercise, you could generalize this for $a^2 = e$, $a b^n a = b^m$. –  Mikko Korhonen Mar 22 '13 at 13:34

$$b^{49} = (b^7)^7 = (ab^4a)^7 = a (b^7)^4 a = a (a b^4 a)^4 a = b^{16}.$$

share|improve this answer

Since $a$ is its own inverse, $b^4 = ab^7a = ab^8b^{-1}a = ab^4a ab^4a ab^{-1}a = b^{14} ab^{-1}a$. Therefore, $ab^{-1}a = b^{-10}$. Inverting both, $aba = b^{10}$. Now, $b^7 = ab^4a = abaabaabaaba = b^{40}$ gives the result.

share|improve this answer
    
Nice solution.! –  nameless Mar 22 '13 at 6:17

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.